Solid lipid nanoparticles of cholesteryl butyrate inhibit the proliferation of cancer cells in vitro and in vivo models. (27th August 2013) - Minelli, R; Occhipinti, S; Gigliotti, C L; Barrera, G; Gasco, P; Conti, L; Chiocchetti, A; Zara, G P; Fantozzi, R; Giovarelli, M; Dianzani, U; Dianzani, C
<x xml:space="preserve">Abstract</x> Background and Purpose Solid lipid nanoparticles containing cholesteryl butyrate (cholbut SLN) can be a delivery system for the anti‐cancer drug butyrate. These nanoparticles inhibit adhesion of polymorphonuclear and tumour cells to endothelial cells and migration of tumour cells, suggesting that they may act as anti‐inflammatory and anti‐tumour agents. Here we have evaluated the effects of cholbut SLN on tumour cell growth using in vitro and in vivo models. Experimental Approach Cholbut SLNs were incubated with cultures of four tumour cell lines, and cell growth was analysed by assessing viability, clonogenic capacity and cell cycle. Effects on intracellular signalling was assessed by Western blot analysis of Akt expression. The in vivo anti‐tumour activity was measured in two models of PC‐3 cell xenografts in SCID/Beige mice. Key Results Cholbut SLN inhibited tumour cell line viability, clonogenic activity, Akt phosphorylation and cell cycle progression. In mice injected i.v. with PC3‐Luc cells and treated with cholbut SLN, . in vivo optical imaging and histological analysis showed no metastases in the lungs of the treated mice. In another set of mice injected s.c. with PC‐3 cells and treated with cholbut SLN when the tumour diameter reached 2 mm, analysis of the tumour dimensions showed that treatment with cholbut SLN substantially delayed tumour growth. Conclusion and Implications Cholbut SLN were effective in inhibiting tumour growth in vitro and in vivo. These effects may involve, in part, inhibition of Akt phosphorylation, which adds another mechanism to the activity of this multipotent drug.